2023
DOI: 10.1111/gbb.12842
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of neural activity and neuroinflammatory factors in the insular cortex of mice with corneal neuropathic pain

Abstract: Dry eye disease (DED) affects nearly 55% of people worldwide; several studies have proposed that central sensitization and neuroinflammation may contribute to the developing corneal neuropathic pain of DED, while the underlying mechanisms of this contribution remain to be investigated. Excision of extra orbital lacrimal glands established the dry eye model. Corneal hypersensitivity was examined through chemical and mechanical stimulation, and open field test measured the anxiety levels. Restingstate fMRI is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For instance, central corneal neuropathic pain is reportedly associated with lower corneal esthesiometry results compared to peripheral corneal neuropathic pain and people without neuropathic pain (Leonardi et al, 2023). Furthermore, functional magnetic resonance imaging (fMRI) has also been used in studying corneal neuropathic pain, just like trigeminal neuralgia; hence, it may help to diagnose corneal neuropathic pain (Choudhury et al, 2022;Xu et al, 2023). A recent study has shown greater activity in fMRI in people with corneal neuropathic pain compared to healthy controls (Choudhury et al, 2022).…”
Section: Significancementioning
confidence: 99%
See 4 more Smart Citations
“…For instance, central corneal neuropathic pain is reportedly associated with lower corneal esthesiometry results compared to peripheral corneal neuropathic pain and people without neuropathic pain (Leonardi et al, 2023). Furthermore, functional magnetic resonance imaging (fMRI) has also been used in studying corneal neuropathic pain, just like trigeminal neuralgia; hence, it may help to diagnose corneal neuropathic pain (Choudhury et al, 2022;Xu et al, 2023). A recent study has shown greater activity in fMRI in people with corneal neuropathic pain compared to healthy controls (Choudhury et al, 2022).…”
Section: Significancementioning
confidence: 99%
“…The interaction between proinflammatory neuropeptides and pain-stimulating cytokines establishes feedback, enabling the continuation of both inflammation and pain, commonly referred to as neuropathic pain. Corneal nerve injury interferes with the transmission of these receptors to the trigeminal ganglion and the projections to the thalamus and somatosensory cortex, instigating sensations of pain and discomfort (Choudhury et al, 2022;Xu et al, 2023;Yan et al, 2020). Apart from inflammation enhancing the activity of existing receptors via phosphorylation, it also causes the de novo transcription of additional ion channels (Goldstein et al, 2019;Sachs et al, 2002;Tran et al, 2000).Altered signaling of many channels, including voltage-gated sodium (Nav1.7-1.9), potassium, and calcium channels, issues downstream effector pathways.…”
Section: Mechanism Of Photoallodynia and Neuropathic Changesmentioning
confidence: 99%
See 3 more Smart Citations